2021
DOI: 10.1097/cin.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Adoption of Electronic Health Record Systems from the Perspective of Nurses

Abstract: This study report aimed to investigate the barriers to implementation of electronic health record systems from the perspective of nurses. The research data comprised responses from nurses working in a university hospital. Our data collection instruments were the Participant Information Form and EHR Nurse Opinion Questionnaire, which were developed by the researchers. Data analysis was presented as summary statistics, including mean values of variables, standard deviation, frequency, and percentages. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The obstacles experienced by nurses in using electronic documentation are problems with the system, including difficulties in accessing the system (poor internet connection, EMR system down, takes a long time to open medical records), which have an impact on services in the form of delays in (Erny Kristiana et al) work, not ready to face system changes, limited resources, imperfect system integration, noncompliance of nurses in documenting nursing care in electronic medical records. The results of this study are in line with the results of several previous studies, which show that limited resources and time, non-optimal procedures, limited access to information, and inadequate training/technical support are obstacles to using electronic documentation (Arikan et al, 2021;Gesulga et al, 2017;Mahalli, 2015;Murphy et al, 2019;Tsai et al, 2020). Human resources (user resistance and lack of skills) and process resources (concerns about return on investment and lack of administrative and political support) are key barriers to overcome (Gesulga et al, 2017).…”
Section: 2discussionsupporting
confidence: 88%
“…The obstacles experienced by nurses in using electronic documentation are problems with the system, including difficulties in accessing the system (poor internet connection, EMR system down, takes a long time to open medical records), which have an impact on services in the form of delays in (Erny Kristiana et al) work, not ready to face system changes, limited resources, imperfect system integration, noncompliance of nurses in documenting nursing care in electronic medical records. The results of this study are in line with the results of several previous studies, which show that limited resources and time, non-optimal procedures, limited access to information, and inadequate training/technical support are obstacles to using electronic documentation (Arikan et al, 2021;Gesulga et al, 2017;Mahalli, 2015;Murphy et al, 2019;Tsai et al, 2020). Human resources (user resistance and lack of skills) and process resources (concerns about return on investment and lack of administrative and political support) are key barriers to overcome (Gesulga et al, 2017).…”
Section: 2discussionsupporting
confidence: 88%
“…For example, in a recent survey of wound care clinicians, predominantly nurses, in the United Kingdom (UK) almost none used contemporary smartphone technology in their practice despite 99% of study participants having access to smartphones and 58% having access to more than one device (Wynn & Clark, 2022a, 2022b). Similar findings have been noted in relation to the adoption of electronic health records (Arikan et al, 2021) despite being a key focus of contemporary digitalization efforts which have repeatedly failed to materialize for over 20 years (Burke, 2002; Rumball‐Smith et al, 2020). This may be due, in part, to resistance to an ever‐shifting technological landscape.…”
Section: Introductionsupporting
confidence: 74%
“…Of the 41 studies that included the EMR user perspective, 19 (46%) reported a usability metric, and 11 (58%) of these reported a positive sentiment [ 50 , 54 , 68 , 70 , 71 , 72 , 76 , 82 , 83 , 89 , 99 ]. Survey components that investigated usability used outcomes such as “ease of use,” “user friendly,” and “technical quality.”…”
Section: Resultsmentioning
confidence: 99%
“…A total of 30% (14/41) of the studies discussed the experience of adapting existing workflows to integrate the new digital interface and transitioning to a digital environment on the wards [ 47 , 50 , 56 , 60 , 64 , 66 , 70 , 71 , 75 , 77 , 93 , 98 , 99 , 101 ]. Generally, the adaptation outcome had a negative sentiment from EMR users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation